ANALISIS KAPASITAS PROFIL BAJA WIDE FLANGE YANG EFISIEN SEBAGAI ELEMEN BALOK, KOLOM, DAN BALOK-KOLOM PADA STRUKTUR GEDUNG (Analisis Terhadap Profil IWF dan HCS Berdasarkan SNI 1729:2015) - Anggara, Jeirry; Wahyuni, Ade Sri; Islam, Mukhlis (Inersia: Jurnal Teknik Sipil, 2024)
The design of the steel frame structure for beam, column and beam-column elements which takes quite a lot of time makes engineers it difficult forin the field of building construction. Engineers have to do several experiments to findsteel profiles IWF and HCS that are safe, efficient and economical. The problems that arise due to the length of the design process are the basis for this research. The research was conducted on 100 profiles IWF and HCS which consisted of 81 profiles IWF and 19 profiles HCS. The analysis was carried out with reference to SNI 1729:2015. The results of this study are in the form of moment capacity graphs and tables of axial capacity of steel profiles as well as coefficients of m and U. Moment capacity graphs and tables of axial capacity of IWF and HCS profiles produced can assist in designing safe and efficient steel profiles as beam, column and column elements. column beam. Efficiency testing of steel profiles used as beam-column elements proves that the safety profile of the axial resisting profile and ultimate moment is close to the value 1.